2003
DOI: 10.1063/1.1558097
|View full text |Cite
|
Sign up to set email alerts
|

Seed layer characterization for PtMn bottom spin-filter spin valves

Abstract: The effect of seed layers on the giant magnetoresistance (GMR) response of bottom spin-filter spin valves (SFSVs) of the structure (seed layer)/PtMn/CoFe/Cu/CoFe/NiFe/Cu/Ta have been studied in detail. Four types of seed layers, NiFeCr, Ta/NiFeCr, NiFeCr/NiFe, and Ta/NiFe were used. The GMR response has been found to be very sensitive to the type and the thickness of the seed layers, which determine the crystallographic quality of the films and the degree of the fcc to fct phase transformation of the PtMn crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…It is evident that critical NiFeCr thickness needs to be 433 Å (when used in combination with 10 Å of CoFe here). This thickness is 450 Å when single NiCr or NiFeCr seed layer is used, which is in agreement with what Lee et al [10,11,14] reported previously.…”
Section: Article In Presssupporting
confidence: 91%
See 1 more Smart Citation
“…It is evident that critical NiFeCr thickness needs to be 433 Å (when used in combination with 10 Å of CoFe here). This thickness is 450 Å when single NiCr or NiFeCr seed layer is used, which is in agreement with what Lee et al [10,11,14] reported previously.…”
Section: Article In Presssupporting
confidence: 91%
“…Those interfaces can significantly affect the AFM texture development (and the corresponding AFM pinning field and blocking temperature), SAF coupling strength, interface spin-dependent electron scattering, and thus the achievable overall GMR performance. For example, it has been found that the seed layer material selection [9][10][11][12][13], critical seed layer thickness [10,11,14], oxygen impurity content [15] had strong impact on the AFM texture growth, its grain size, and the corresponding GMR ratio of the film stack. Background impurity effect can be more profound when high oxygen-affinity seed layer (like Ta) is used.…”
Section: Introductionmentioning
confidence: 99%
“…Additional to the UDA, several thermal annealing steps up to 250 C are required in the process of device fabrication for curing organic insulators coated on the metal surfaces [5]. The degree of FCC-FCT transformation, the H ex and the resulting GMR performance of top or bottom SVs are affected by annealing temperature, PtMn thickness and seed layers [2,[6][7][8][9]. In PtMn-based top SVs with a Ta/ NiFe seed layer, the FCC-FCT ordering degree is saturated after 6 h UDA by using a vacuum furnace at 370 C and under a magnetic field of 1 kOe [6].…”
Section: Introductionmentioning
confidence: 99%
“…The seed layer used for this study was not disclosed by the authors. Recently, the GMR response of the bottom spin-filter SV heads (SFSVs) was found to be very sensitive to the type and thickness of the seed layers, which determine the crystallographic quality of the films and the degree of the PtMn FCC to FCT phase transformation [9]. The authors reported a higher GMR response by using NiFeCr/NiFe or Ta/NiFeCr seed layers [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation